Pemberdayaan Keterampilan Berpikir Kritis Melalui Pembelajaran Process Oriented Guided Inquiry Learning (POGIL) - Eka Ariyati; Herawati Susilo; Hadi Suwono; Fatchur Rohman (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This study aims to examine the potential of the process oriented guided inquiry learning (POGIL) model in empowering students' critical thinking skills in learning. This research is a library research on relevant theories and research results. The results showed that so far learning has not taught critical thinking in class. Critical thinking skills is a basic skill that can help students analyze arguments, make conclusions using reasoning, assess or evaluate, and make decisions or solve problems. Through POGIL, students actively think critically at each stage of their learning. The POGIL stages are orientation, exploration, concept formation, application, and closure.